2012
DOI: 10.1371/journal.pone.0035441
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Francisella tularensis Subspecies holarctica Live Vaccine Strain in the Tick Vector Dermacentor variabilis

Abstract: BackgroundThe γ-proteobacterium Francisella tularensis is the etiologic agent of seasonal tick-transmitted tularemia epizootics in rodents and rabbits and of incidental infections in humans. The biology of F. tularensis in its tick vectors has not been fully described, particularly with respect to its quanta and duration of colonization, tissue dissemination, and transovarial transmission. A systematic study of the colonization of Dermacentor variabilis by the F. tularensis subsp. holarctica live vaccine strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Microscopic (25), epidemiological (5,26), and relatively recent experimental (9,10,16) evidence implicates several tick species as major natural reservoirs for F. tularensis. A goal of these studies was to establish a quantitative tick infection model to determine if replication occurs and to follow its kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microscopic (25), epidemiological (5,26), and relatively recent experimental (9,10,16) evidence implicates several tick species as major natural reservoirs for F. tularensis. A goal of these studies was to establish a quantitative tick infection model to determine if replication occurs and to follow its kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been shown that transmission for type A and B strains from adult D. variabilis females to mice occurs shortly after attachment (10), possibly supporting a mechanism of transmission from tick salivary glands directly into the skin. Using a capillary feeding model of D. variabilis infection, F. tularensis was found to initially colonize the tick midgut and then disseminate to the hemolymph and salivary glands (16). To determine the localization of bacteria in tick tissues and to quantify the relative number of bacteria in each tissue, we infected nymphal D. variabilis ticks with LVS or LVS strains containing pFNLTP6 gro-GFP or gro-TURBO red and performed fluorescence microscopy on harvested midgut or salivary gland tissues.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirm those of a previous report in which F. tularensis LVS colonized capillary‐fed Dermacentor variabilis (Mani et al . ). To investigate the bacterial factors associated with bacterial growth in ticks, a hlyD mutant was constructed in F. tularensis LVS and microinjected into ticks.…”
Section: Resultsmentioning
confidence: 97%
“…Vector Control-Development and Improvement of the Modern Chemical Insecticides 2 obtained by microscopic, immunofluorescent, biochemical techniques and other methods, through which the knowledge about the mode of transmission of various infections is becoming objective and specified [6,7].…”
Section: David Publishingmentioning
confidence: 99%